Fuel consumption and emission reduction of marine lean-burn gas engine employing a hybrid propulsion concept. (August 2022) - Tavakoli, Sadi; Bagherabadi, Kamyar Maleki; Schramm, Jesper; Pedersen, Eilif
As the emission legislation becomes further constraining, all manufacturers started to fulfill the future regulations about the prime movers in the market. Lean-burn gas engines operating under marine applications are also obligated to enhance the performance with a low emission level. Lean-burn gas engines are expressed as a cleaner source of power in steady loading than diesel engines, while in transient conditions of sea state, the unsteadiness compels the engine to respond differently than in the steady-state. This response leads to higher fuel consumption and an increase in emission formation. In order to improve the stability of the engine in transient conditions, this study presents a concept implementing a hybrid configuration in the propulsion system. An engine model is developed and validated in a range of load and speed by comparing it with the available measured data. The imposed torque into the developed engine model is smoothed out by implementing the hybrid concept, and its influence on emission reduction is discussed. It is shown that with the hybrid propulsion system, the NOX reduces up to 40% because of the maximum load reduction. Moreover, eliminating the low load operation by a Power Take In during incomplete propeller immersion, the methane slip declines significantly due to combustion efficiency enhancement.